Fire retardant coating for new energy battery, coating preparation method and battery
By using a single-component UV-moisture dual curing system and a combination of expansion materials, charcoal-forming reinforced fillers, and aerogel particles in power battery fire-retardant coatings, the problems of insufficient thermal insulation and fire resistance performance and long curing time in existing coatings in high temperature environments are solved, and rapid curing and excellent thermal insulation and fire resistance are achieved, effectively preventing the "thermal runaway" effect.
Patent Information
- Application Number
- CN202310873482.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The existing power battery fireproof coatings are difficult to effectively insulate and fireproof in high temperature environments, and the curing time is long, which limits its application in industrial assembly line production.
New energy battery fireproof coatings using a single-component UV-moisture dual curing system are used to achieve rapid curing and excellent thermal insulation and fire resistance by spraying and curing under ultraviolet light, combined with expanded materials, charcoal-forming reinforced fillers and aerogel particles.
The coating achieves surface curing for about 1 minute under ultraviolet light, and achieves the best performance after a week of dark curing. It has good mechanical properties and thermal insulation and fire resistance. It can last for more than 60 minutes under a flame of 1000℃, keeping the substrate temperature below 400℃, effectively avoiding or delaying the "thermal runaway" effect.
Smart Images

Figure CN116925632B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a fire retardant coating for new energy batteries, a coating preparation method and a battery. Background Art
[0002] The battery pack of power batteries and energy storage batteries is usually composed of multiple single battery modules. Mechanical damage, thermal shock, internal short circuit, long-term continuous and frequent fast charging in high temperature environment, etc. may lead to "thermal runaway" of individual single batteries. "Thermal runaway" will spread and cause the temperature of the surrounding single batteries to rise rapidly, and the temperature can be as high as 500 to 1000 degrees Celsius, eventually leading to the catastrophic consequences of the entire battery pack burning and exploding. In terms of battery thermal management, due to the high density of mica boards and the fact that they are rigid materials that are not easy to deform, it is difficult to fully fit with the battery, while traditional aerogels are expensive and cannot withstand the high temperature generated by battery explosions during thermal runaway. In this context, high-performance coating solutions that can provide safety for power batteries have become an emerging market that coatings companies have continued to pay attention to in recent years.
[0003] At present, fire retardant coatings are mainly based on the expansion fire-resistant mechanism. When heated, the heat energy in the coating is converted. The fire retardant coating can quickly expand dozens of times and absorb the surrounding heat, thereby effectively preventing high temperature from invading the substrate it protects, and thereby achieving the purpose of fire prevention. According to the requirements of the internal and external space of the automotive battery pack, the construction thickness of the battery box fire retardant coating is 0.8 to 1.5 mm, and the inside and outside of the battery pack cover are generally sprayed. At present, domestic and foreign power battery coating suppliers, including PPG, Akzo Nobel, Lenke Weiser (Germany), Axalta, Sherwin-Williams, Nippon Paint and other companies, have achieved the commercialization of power battery fire retardant coatings through two-component solvent-free epoxy solutions or powder coating solutions. The main components of this type of fire retardant coating include film-forming substances, carbon sources, acid sources, foaming agents, fillers, etc. Among them, the film-forming substances are generally acrylic resins, epoxy resins or fluoropolymers, etc. After the power battery pack is coated, it is difficult to take into account the thermal insulation performance between the cells (the thermal conductivity of the mainstream fire retardant coatings in the market is usually 0.2W / mK); the coating systems of domestic and foreign teams, whether water-based, solvent-based or solvent-free, have the disadvantages of long surface drying and curing time. For example, the solvent-free epoxy system requires 2-5 hours of surface drying time, and the water-based acrylic system requires about 6-8 hours of surface drying. The long drying time will undoubtedly greatly reduce the production efficiency, especially it is difficult to apply in industrial assembly line production, which greatly limits the use of these products on the battery shell. Powder coatings require high-temperature baking and curing at 150-220℃ for more than 30 minutes, and the maximum baking temperature of the battery cannot exceed 80℃, and there are problems such as low powder coating rate and uneven edge thickness. Summary of the invention
[0004] In response to the deficiencies in the prior art, the present application provides a fire-retardant coating, a coating preparation method and a battery for new energy batteries. The coating is sprayed on the surface of a substrate and can be surface cured by ultraviolet light exposure for about 1 minute. Its rapid curing characteristics are suitable for battery assembly line production, which can greatly improve battery production efficiency. The prepared coating has stable mechanical properties and excellent thermal insulation and fire retardant properties.
[0005] The technical solutions adopted in this application are as follows:
[0006] In the first aspect, a fire retardant coating for a new energy battery is provided in the embodiments of the present application, and includes the following components by mass percentage:
[0007]
[0008] In the above technical scheme, further, the UV monomer is selected from one or more of IBOA (isobornyl methacrylate), TPGPA (tripropylene glycol diacrylate), THFA (tetrahydrofuran acrylate), DEGDA (diethylene glycol diacrylate), TGICA (epoxypropyl isocyanurate acrylate), and hexanediol diacrylate (HDDA); the UV photoinitiator is one or more of 819, 907, 369, 1173, ITX, 184, and BP.
[0009] Furthermore, the hydrolysis-resistant saturated polyester resin should have a hydroxyl value of ≥6KOHmg / g and a tensile strength of ≥300Mpa.
[0010] Furthermore, the aerogel particles are biomass-reinforced montmorillonite aerogel, silicon-based aerogel or carbon nanotube aerogel.
[0011] Furthermore, the solvent is one or more of ethyl acetate, butanone, acetone, propylene glycol methyl ether acetate, and xylene.
[0012] Furthermore, the carbon-forming reinforcing filler is one or more of titanium dioxide, zinc borate, expanded graphite, and nano-silicon dioxide; the expandable filler is one or more of expanded graphite, or a mixture of APP (ammonium polyphosphate), PER (pentaerythritol), and MEL (melamine) in a mass ratio of 2:1:1.
[0013] In a second aspect, the present application provides a method for preparing a new energy battery fire retardant coating, comprising:
[0014] Apply the primer for the first time on the surface to be sprayed after surface treatment, and then UV cure;
[0015] After that, the fire retardant coating is sprayed for the second time and UV cured;
[0016] Then spray the fire retardant coating for the third time and UV cure it;
[0017] Finally, moisture cures;
[0018] Wherein, the fire retardant coating is any of the fire retardant coatings described above, and the primer formula is based on any of the fire retardant coatings described above, removing aerogel particles, carbon-forming reinforcing fillers, and expanding filler components, and includes, by mass:
[0019]
[0020] Furthermore, the thickness of the primer layer in the fire retardant coating is controlled to be 50-80 μm, the thickness of a single layer of the fire retardant coating is 0.3-0.5 mm, and the total thickness of the fire retardant coating is 0.6-1 mm.
[0021] Furthermore, the surface to be sprayed is the surface of the battery cell, or an insulating film substrate, and an insulating pressure-sensitive adhesive is coated on the other side of the film substrate and pasted on the surface of the battery cell to achieve insulation, heat insulation and fire protection for the battery cell. The film substrate can be PET, PI, PP, PE and other materials, and the pressure-sensitive adhesive can be an acrylic pressure-sensitive adhesive.
[0022] In a third aspect, an embodiment of the present application provides a fire retardant coating, which is prepared by any of the above methods.
[0023] In a fourth aspect, an embodiment of the present application provides a new energy battery, the surface of the battery cell of which contains a fire-retardant coating prepared by any of the above methods.
[0024] The beneficial effects of the present invention are:
[0025] The coating of the present invention adopts a single-component UV-moisture dual curing system, preferably an expansion material, a carbon-forming reinforcing filler, and a coupled aerogel particle. The coating is sprayed on the surface of the substrate and irradiated with ultraviolet light for about 1 minute to achieve surface curing, and dark curing for about a week to achieve optimal performance. Compared with other similar products on the market, the rapid curing characteristics of the coating of the present invention are suitable for industrial assembly line operations and can greatly improve production efficiency. The coating has stable mechanical properties, good insulation withstand voltage, high shear strength, excellent moisture and heat resistance, and excellent thermal insulation and fireproof properties. When heated, the initial coating with a thickness of 0.5-1mm expands to form a flame retardant layer, which can withstand a flame of 1000°C for more than 60 minutes, while keeping the temperature of the substrate below 400°C, effectively avoiding or delaying the spread of the "thermal runaway" effect.
[0026] The coating made of the fireproof coating of the present invention meets the following indicators: shear and pull-out strength>10MPa, impact resistance>50cm; surface resistance>2GΩ, leakage current<1mA; after double 85 and hot and cold cycle for 1000h: shear and pull-out strength attenuation<30%, surface resistance>500MΩ, leakage current<1mA; fire resistance>1h, coating thermal conductivity<0.05W / mK, etc. The performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the fire retardant coating and flame retardancy of an embodiment of the present application;
[0028] Figure 2 A schematic diagram of the preparation process of the fire retardant coating of an embodiment of the present application; DETAILED DESCRIPTION
[0029] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0030] The present application embodiment relates to a fire retardant coating for new energy batteries, which may include the following components by weight:
[0031] Epoxy acrylate 3-10%, preferably 5%;
[0032] Polyurethane acrylate 15-30%, preferably 20%; wherein epoxy acrylate and polyurethane acrylate are the main resins of the coating, providing film-forming carriers, and the peeling force, shearing and pulling after subsequent curing;
[0033] UV monomer 20-30%, preferably 25%; the UV monomer can be selected from one or more of IBOA (isobornyl methacrylate), TPGPA (tripropylene glycol diacrylate), THFA (tetrahydrofuran acrylate), DEGDA (diethylene glycol diacrylate), TGICA (epoxypropyl isocyanurate acrylate), hexanediol diacrylate (HDDA);
[0034] UV photoinitiator 1-5%; the UV photoinitiator can be one or more of 819, 907, 369, 1173, ITX, 184, BP; UV monomer plays the role of diluting and dissolving UV initiator, and the initiator is cracked under the action of UV light to provide free radicals, which initiates the polymerization of double bonds in prepolymer and monomer;
[0035] 1-8% hydrolysis-resistant saturated polyester resin, preferably 4%; saturated polyester resin improves the cohesion, flexibility, adhesion, shear and tensile strength of the coating, and its hydroxyl content should be ≥6KOHmg / g, and the tensile strength should be ≥300Mpa;
[0036] Leveling agent 0.1-0.5%, preferably 0.3%;
[0037] Defoaming agent 0.1-0.5%, preferably 0.3%;
[0038] Aerogel particles 5-15%, aerogel particles can be biomass-enhanced montmorillonite aerogel, silicon-based aerogel or carbon nanotube aerogel, especially biomass-enhanced montmorillonite aerogel particles can achieve the best effect, and the preparation method can be adding montmorillonite to a 2% biomass aqueous solution with stirring and heating reaction, low-temperature drying at -50°C for 24h, and then drying at 80°C for 4h; wherein the biomass material can be one or more of carboxymethyl cellulose, cyclodextrin, chitosan, polyvinyl alcohol fiber, and seaweed fiber.
[0039] 3-13% of carbon-forming reinforcing filler; it can be one or more of titanium dioxide, zinc borate, expanded graphite, and nano-silicon dioxide, preferably 1-4% of titanium dioxide, 1-3% of zinc borate, 1-4% of expanded graphite, and 0.1-2% of nano-silicon dioxide;
[0040] 15-40% of the expansion filler; it can be a mixture of APP (ammonium polyphosphate), PER (pentaerythritol), and MEL (melamine) in a mass ratio of 2:1:1, wherein the aerogel particles, the carbon-forming reinforcing filler, and the expansion filler are coordinated to expand after encountering fire to form a flame retardant layer and enhance the strength of the carbon layer after expansion, reduce smoke generation, and can provide good heat insulation and reduce the thermal conductivity of the coating;
[0041] The solvent is the balance; the solvent may be one or more of ethyl acetate, butanone, acetone, propylene glycol methyl ether acetate, and xylene;
[0042] Color paste 1-2%, can be added according to specific needs. The sum of all components is 100%.
[0043] like Figure 1 As shown, the coating prepared by the coating of the present application according to the method, before being heated, provides insulation and heat insulation protection for the battery cell under normal circumstances due to the high heat barrier performance of the coating; when the coating encounters extreme conditions, such as temperatures above 150°C, the components that expand from the outside to the inside of the coating gradually decompose under heat, releasing gas, and the coating foams into carbon, coupling the thermal insulation and fire resistant properties of the aerogel, reducing the temperature of the thermal runaway part, isolating the abnormality, and preventing the thermal runaway from spreading.
[0044] The coating production process of the embodiment of the present application:
[0045] UV monomer, saturated polyester resin, solvent were added to polyurethane acrylate and epoxy acrylate prepolymers, followed by expansion filler, aerogel particles, carbon-forming reinforcing filler, leveling agent, defoamer, and color paste, stirred and dispersed at 800-1200 rpm for 30 minutes, and the whole was passed through a grinder. After reaching the required fineness, photoinitiator was added in a dark place, and stirred and dispersed at 300-500 rpm for 10 minutes. Filtered, sealed and stored in a light-shielding container. The performance test of the obtained coating is shown in Table 1.
[0046] Table 1. Coating performance test
[0047]
[0048]
[0049] The fire-retardant coating structure of the embodiment of the present application: the thickness of the primer is 50-80 μm, the thickness of the single layer of the fire-retardant coating is 0.3-0.5 mm, and a protective coating with a total thickness of 0.6-1 mm is formed by 1 layer of UV primer, 2 layers of UV fire-retardant coating, and 3 sprays and 3 solids; the power of the UV lamp is 5000-8000 mW / m 2 , light exposure time 10-90s. After UV initial curing, it is cured in moisture (room temperature, humidity 50-80% RH) for 1 week to improve the mechanical properties of the coating. Figure 2 shown.
[0050] Example
[0051]
[0052]
[0053] Comparative Example
[0054]
[0055]
[0056] In the above example, the UV monomer is IBOA, the photocuring agent 1 is ITX, the photocuring agent 2 is 907, and the aerogel is biomass-reinforced montmorillonite aerogel particles;
[0057] In the above comparative examples, the UV monomer is IBOA, the photocuring agent 1 is ITX, the photocuring agent 2 is 907, and the aerogels except for comparative example 2 are biomass-reinforced montmorillonite aerogel particles. The difference between comparative example 1 and example 1 is that there is no expanding filler; the difference between comparative example 2 and example 1 is that there is no aerogel; the difference between comparative example 3 and example 1 is that there is no carbon-forming reinforcing material such as titanium dioxide, expanded graphite and nano-silicon dioxide; the difference between comparative example 4 and example 1 is that there is no saturated polyester resin; the difference between comparative example 5 and example 1 is that there is no primer layer but the curing process remains unchanged; the difference between comparative examples 6 and 7 and example 1 is the different thickness of the fire retardant topcoat; the difference between comparative examples 8 and 9 and example 1 is the different thickness of the primer layer.
[0058] It can be seen that the coating of the present invention optimizes the components, preferably expandable materials and carbon-forming reinforcing fillers, couples the synergistic effect of aerogel particles with high fire resistance and high thermal barrier properties, and adopts a single-component UV-moisture dual curing system to achieve a coating that can be quickly cured and maintains excellent mechanical stability and excellent thermal insulation and fireproof properties; the coating of the present invention achieves surface curing in about 1 minute of ultraviolet light, and achieves optimal performance after about a week of dark curing. Compared with other similar products on the market, its rapid curing characteristics are suitable for industrial assembly line operations and can greatly improve production efficiency. The coating has stable mechanical properties, good insulation withstand voltage, high shear strength, excellent moisture and heat resistance, and excellent fireproof performance. When heated, the initial coating of 0.5-1mm thickness expands to form a flame retardant layer. Combined with the efficient barrier properties of aerogel nanoparticles, it can withstand a flame of 1000°C for more than 60 minutes, while keeping the temperature of the substrate below 400°C, effectively avoiding or delaying the spread of the "thermal runaway" effect. On this basis, the coating of the present invention combines the application conditions of new energy batteries, taking into account the thermal barrier properties between battery cells in high temperature extreme environments, and comprehensively reducing the risk of battery pack combustion and explosion. In addition, the solution of the present invention can combine insulation and fireproof and heat-insulating properties together to simplify the safety protection structure of new energy batteries.
[0059] At the same time, the low energy consumption, low emissions, high environmental protection of raw materials, and greatly improved production efficiency of the preparation process of the present invention will gain a strong competitive advantage in the green thermal insulation material market.
[0060] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0061] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A fire retardant coating for new energy batteries, characterized in that: According to mass percentage, it includes the following components: The aerogel particles are biomass-enhanced montmorillonite aerogels, and the preparation method thereof is to add montmorillonite to a 2% biomass aqueous solution, stir and heat for reaction, dry at -50°C for 24 hours, and then dry at 80°C for 4 hours; wherein the biomass material is one or more of carboxymethyl cellulose, cyclodextrin, chitosan, polyvinyl alcohol fiber, and seaweed fiber; The carbon-forming reinforcing filler is one or more of titanium dioxide, zinc borate, expanded graphite, and nano-silicon dioxide; the expandable filler is one or more of expanded graphite, or a mixture of APP (ammonium polyphosphate), PER (pentaerythritol), and MEL (melamine) in a mass ratio of 2:1:1; The hydrolysis-resistant saturated polyester resin has a hydroxyl value of ≥6KOHmg / g and a tensile strength of ≥300Mpa; the UV monomer is selected from one or more of IBOA (isobornyl acrylate), TPGDA (tripropylene glycol diacrylate), THFA (tetrahydrofuran acrylate), DEGDA (diethylene glycol diacrylate), TGICA (glycidyl isocyanurate acrylate), and hexanediol diacrylate (HDDA); the UV photoinitiator is one or more of 819, 907, 369, 1173, ITX, 184, and BP.
2. The fire retardant coating for new energy batteries according to claim 1, characterized in that: The solvent is one or more of ethyl acetate, butanone, acetone, propylene glycol methyl ether acetate and xylene.
3. A method for preparing a fireproof coating for a new energy battery, characterized in that: include: Apply the primer for the first time on the surface to be sprayed after surface treatment, and then UV cure; After that, the fire retardant coating is sprayed for the second time and UV cured; Then spray the fire retardant coating for the third time and UV cure it; Finally, moisture cures; Wherein, the fire retardant coating is the fire retardant coating as claimed in any one of claims 1-2, and the primer formula is the fire retardant coating as claimed in any one of claims 1-2 without aerogel particles, carbon-forming reinforcing fillers, and expanding fillers, and comprises, by weight:
4. The method for preparing the fire retardant coating of new energy batteries according to claim 3, characterized in that: The thickness of the primer layer in the fire retardant coating is controlled to be 50-80μm, the thickness of the single layer of the fire retardant coating is 0.3-0.5mm, and the total thickness of the fire retardant coating is 0.6-1mm.
5. The method for preparing the fire retardant coating of new energy batteries according to claim 3, characterized in that: The surface to be sprayed is the surface of the battery cell, or a film substrate, and a pressure-sensitive adhesive is coated on the other side of the film substrate and pasted on the surface of the battery cell.
6. A new energy battery, characterized in that: The surface of the battery core contains a fireproof coating prepared by the method as claimed in claim 3.
Citation Information
Patent Citations
Doubly solidified coloring UV nanometer paint
CN106366901A
UV-curable fireproof coating material, preparation method and applications thereof
CN110698958A
Water-based indoor intumescent fire-retardant coating for steel structure and preparation method thereof
CN112708316A